1987
DOI: 10.1070/qe1987v017n12abeh011249
|View full text |Cite
|
Sign up to set email alerts
|

Investigation of physical processes in the active medium of a pulsed CO2laser responsible for variation of the laser frequency during a pulse

Abstract: We suppose that the solar neutrino problem is due only to the mechanism introduced by Ellis, Hagelin, Nanopoulos and Srednicki (EHNS) to allow pure quantum states to evolve into mixed ones. Lower limits on the EHNS parameters (α, β, γ ) are obtained. We find that γ 7.4 × 10 −22 GeV if α < 2γ and α 1.5 × 10 −21 GeV if α > 2γ , with no constraint on β. This limit is consistent with the upper limits extracted from the K 0 − K 0 system and can be detected in future experiments.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

0
2
0

Year Published

1989
1989
2011
2011

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(2 citation statements)
references
References 10 publications
0
2
0
Order By: Relevance
“…However, it has been found that even in single frequency systems, the "instantaneous" emission frequency ν g varies, i.e., sweeping of the frequency occurs. Particular aspects of frequency variation in pulsed CO 2 lasers have been examined elsewhere [4,[7][8][9][10]. The frequency sweeping present in the initial laser output is also transferred to the light converted by means of nonlinear crystals.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…However, it has been found that even in single frequency systems, the "instantaneous" emission frequency ν g varies, i.e., sweeping of the frequency occurs. Particular aspects of frequency variation in pulsed CO 2 lasers have been examined elsewhere [4,[7][8][9][10]. The frequency sweeping present in the initial laser output is also transferred to the light converted by means of nonlinear crystals.…”
mentioning
confidence: 99%
“…Thus, there is some practical interest in examining the behavior and magnitude of frequency sweep for CO 2 lasers in this case. We assume that the frequency of the laser emission coincides with the longitudinal mode ν c of the laser and obeys the equation [4,[7][8][9][10] ν g (t) = ν c (t) = ν c (0) l 0 n 0 + l a n a (0)…”
mentioning
confidence: 99%